Upaya Menekan Turnover Intention Dengan Prediktor Dukungan Organisasi Melalui Variabel Intervening Kepuasan Kerja Dan Komitmen Organisasi - Yolanda Merlysabella; Didik Subiyanto (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study is to examine and analyze the effect of organizational support on job satisfaction, the effect of organizational support on organizational commitment, the effect of organizational support, job satisfaction, organizational commitment and on turnover intention, the effect of organizational support on turnover intention through job satisfaction and work commitment. The research sample was all employees of the Best City Hotel which found 47 people. The sampling method used is saturated sampling or census. So that the total sample taken in this study amounted to 47 employees. Sample data collection was done by distributing a questionnaire in the form of a Google Form sent via the employee's WhatsApp number. The number of questionnaire data that was processed was 47 questionnaires. Data processing in this study using multiple linear regression analysis techniques, assisted by the SPSS version 23.0 program. The results of this study indicate that organizational support has a positive and significant effect on employee job satisfaction, organizational support has a positive and significant effect on organizational commitment, organizational goals and organizational support have a negative and significant effect on turnover intention, job satisfaction and organizational commitment mediate the effect of organizational support on turnover. intention. Keywords: Job Satisfaction, Organizational Commitment, Organizational Support, Turnover Intention